2021
DOI: 10.7202/1081788ar
|View full text |Cite
|
Sign up to set email alerts
|

Entre croyances et pratiques de futurs enseignants de mathématiques au secondaire : une relation perméable

Abstract: La stabilité des résultats faibles des élèves en mathématiques préoccupe depuis bon nombre d’années les systèmes éducatifs à travers le monde. Si les pratiques pédagogiques enseignantes sont pointées comme un facteur déterminant de l’engagement des élèves et de la qualité de leurs apprentissages, elles ne représentent que la partie émergée de l’iceberg. Beaucoup de travaux ont montré que ces pratiques sont fortement colorées tant par les croyances épistémologiques que par les croyances relatives à l’enseigneme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…Several hypotheses can be put forward to explain the observed changes. Our results support previous work by indicating that teacher candidates enter TE with pre-conceptions built when they were in school (Hanin et al, 2021; Hanin et al, 2022; Liljejedahl et al, 2019; Voss & Kunter, 2021). At the same time, they are in line with the work that has shown that beliefs are permeable to teacher education experiences.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Several hypotheses can be put forward to explain the observed changes. Our results support previous work by indicating that teacher candidates enter TE with pre-conceptions built when they were in school (Hanin et al, 2021; Hanin et al, 2022; Liljejedahl et al, 2019; Voss & Kunter, 2021). At the same time, they are in line with the work that has shown that beliefs are permeable to teacher education experiences.…”
Section: Discussionsupporting
confidence: 91%
“…Regarding the formal conception, if it is hard to uproot, it is probably because of the strong emphasis put by teachers in compulsory education (during the students’ own school career) on the use of symbolism, language, and mathematical vocabulary with an often excessive rigor and undoubtedly also due to the image of mathematics conveyed by society (Beswick & Fraser, 2019; Cratty, 2012). As for the promotion of the application of procedures, several studies have highlighted that novice teachers focus on classroom management (rather than on the management of learning; Bernal Gonzalez et al, 2018) which may explain a marked position in favor of practices that maintain control of the classroom (Hanin et al, 2021; Mukamurera, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations